2016
DOI: 10.4314/tjpr.v15i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of <i>Commiphora molmol</i> Extract against Liver and Kidney Toxicity Induced by Carbon Tetrachloride in Mice

Abstract: Purpose: To explore the protective role of Mirazid® (MRZ), a mixture extracted from Commiphora molmol Engler (Burseraceae), against toxicity induced by carbon tetrachloride (CCl4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…48 Alm Eldeen et al study showed appearance of the necrotic areas, cellular infiltration, atrophied renal glomerular and degeneration renal tubule lining with widening of the renal lumens. 49 The present results revealed widening of glomerular renal space ,vascular congestion , degeneration of epithelial cells of tubules and widening of the tubular lumen after induction nephrotoxicity by CCl4, then the present data is consistent with the previous studies. Our results indicated that the Allium leaves utilization is successful in ameliorating the renal histopathological changes induced by CCl4.…”
Section: Discussionsupporting
confidence: 93%
“…48 Alm Eldeen et al study showed appearance of the necrotic areas, cellular infiltration, atrophied renal glomerular and degeneration renal tubule lining with widening of the renal lumens. 49 The present results revealed widening of glomerular renal space ,vascular congestion , degeneration of epithelial cells of tubules and widening of the tubular lumen after induction nephrotoxicity by CCl4, then the present data is consistent with the previous studies. Our results indicated that the Allium leaves utilization is successful in ameliorating the renal histopathological changes induced by CCl4.…”
Section: Discussionsupporting
confidence: 93%
“…Keeping in view the high sensitivity of kidney to CCl 4 , the formation of less urine by kidneys may cause H 2 O and waste-products to build-up in the blood and body. CCl 4 administration increases ROS levels and leads to oxidative stress which in turn decreases antioxidant enzyme levels ( Alm-Eldeen et al, 2016 , Zangeneh et al, 2018 ). Our study showed declined levels of POD, SOD, GSH, and CAT in CCl 4 -injected group while the co-treatment of PJM/PHM, particularly high dose (400 mg/kg) with CCl 4 markedly (p < 0.05) elevated the levels of antioxidant enzymes, similar to silymarin- treated and control rat group.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, an increased level of TBARS, nitrite, and H 2 O 2 was witnessed in CCl 4 -injected rats. Earlier studies have reported a marked elevation in LPO causing membranous damage and many pathological alterations comprising acute and chronic renal damages ( Alm-Eldeen et al, 2016 ). The pathologies were reversed by treatment with PJM and PHM (400 mg/kg) fractions which is in accordance with the findings of Karakuş et al, 2017 , who stated the extracts of Taraxacum officinale and Silybum marianum to overcome oxidative stress via increasing antioxidant enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, C. molmol resin protected the liver against ethanol-induced hepatotoxicity in rats and decreased the circulating levels of ALT, AST, and ALP [ 51 ]. In addition, treatment with C. molmol resin extract decreased circulating ALT and AST in carbon tetrachloride- (CCl 4 -) [ 52 ] and D-GalN/LPS-induced [ 53 ] liver injury in rats and in a rodent model of chemically induced hepatocarcinogenesis [ 54 ]. The declined body weight in NH 4 Cl-induced hyperammonemic rats could be explained by the decreased body fat content.…”
Section: Discussionmentioning
confidence: 99%